Empowerment in outpatient care for patients with chronic kidney disease - from the family member's perspective - Malm Dan; Wikby Kerstin; Nygårdh Annette; Ahlstrom Gerd (BMC, 2011)
Abstract Background Family members of persons with pre-dialysis chronic kidney disease may experience feelings of vulnerability and insecurity as the disease follows its course. Against this background, the aim of the present study was to explore empowerment in outpatient care as experienced by these family members. Methods An inductive approach for qualitative data analysis was chosen. The study sample comprised 12 family members of pre-dialysis patients at an outpatient kidney clinic. Two interviews with each family member were subjected to content analysis to gain an understanding of empowerment from the family members' perspective. Results Having strength to assume the responsibility was the main theme that emerged from the following five sub-themes: Being an involved participant, Having confirming encounters, Trusting in health-care staff, Comprehending through knowledge, and Feeling left out. Four of these five sub-themes were positive. The fifth subtheme illuminated negative experience, indicating the absence of empowerment. Conclusions Family members' experience of empowerment is dependent on their ability to assume the responsibility for a relative with chronic kidney disease when needed. The findings emphasise the need for a family perspective and the significance of a supportive environment for family members of persons in outpatient care.